Detection theory : a user's guide - Macmillan, Neil A.; Hautus, Michael J.; Creelman, C. Douglas (New York, NY : Routledge, 2022)
"Detection Theory: A User's Guide is an introduction to one of the most important tools for the analysis of data where choices must be made, and performance is not perfect. In these cases, detection theory can transform judgments about subjective experiences, such as perceptions and memories, into quantitative data ready for analysis and modeling. This modern summary of signal detection theory is both a self-contained reference work for users and a readable text for graduate students and researchers learning the material either in courses or on their own"--
Neil Macmillan was first named author on earlier editions.
Keywords: Signal detection (Psychology); PSYCHOLOGY / General; PSYCHOLOGY / Cognitive Psychology; PSYCHOLOGY / Research & Methodology